The Influence of Service Quality and Brand Image on Customer Satisfaction Through Purchase Decision as an Intervening Variable at Mansyur Residence Medan - Putri Lailatul Barqah; Indra Sakti; Adelina Lubis (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2024)
The aim of this research is to assess how service quality and image impact customer satisfaction, with purchase satisfaction serving as an intermediary factor, specifically within Mansyur Residence Medan. The study encompasses a population of 180 individuals, with a sample size determined using a simple random sampling technique, amounting to 124 participants. Data collection is facilitated through a questionnaire focusing on service quality, image, customer satisfaction, and purchase decisions. Data analysis adopts the Partial Least Square (PLS) approach via SmartPLS software. Findings reveal that service quality, image, and purchase decisions significantly and positively influence customer satisfaction. Furthermore, through specific indirect effects, it is evident that service quality positively and significantly affects customer satisfaction via purchase decisions, while image similarly exerts a positive and significant impact on customer satisfaction through purchase decisions. The combined influence of service quality and image on the Customer Satisfaction variable accounts for 76.3%, with the remainder influenced by variables beyond the scope of this study. Similarly, the contribution of the purchase decision variable influenced by service quality and brand image amounts to 79%, with external variables accounting for the remaining influence.